2022
DOI: 10.3389/fcell.2022.834408
|View full text |Cite
|
Sign up to set email alerts
|

Pathways and Mechanisms of Cellular Cholesterol Efflux—Insight From Imaging

Abstract: Cholesterol is an essential molecule in cellular membranes, but too much cholesterol can be toxic. Therefore, mammalian cells have developed complex mechanisms to remove excess cholesterol. In this review article, we discuss what is known about such efflux pathways including a discussion of reverse cholesterol transport and formation of high-density lipoprotein, the function of ABC transporters and other sterol efflux proteins, and we highlight their role in human diseases. Attention is paid to the biophysical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 272 publications
(435 reference statements)
1
31
0
1
Order By: Relevance
“…Accordingly, ABCA1 protein, whose expression levels were increased in an activity-dependent context, appeared downregulated in SMN-depleted stimulated cells. One of downstream effects of the reduced expression levels of ABCA1 is the cytoplasmatic accumulation of cholesterol due to its efflux impairment [21]. Accordingly, in our system we demonstrated an aberrant distribution of cholesterol in siSMN-transfected fibroblasts and, most importantly, in SMA type I patient-derived fibroblasts.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Accordingly, ABCA1 protein, whose expression levels were increased in an activity-dependent context, appeared downregulated in SMN-depleted stimulated cells. One of downstream effects of the reduced expression levels of ABCA1 is the cytoplasmatic accumulation of cholesterol due to its efflux impairment [21]. Accordingly, in our system we demonstrated an aberrant distribution of cholesterol in siSMN-transfected fibroblasts and, most importantly, in SMA type I patient-derived fibroblasts.…”
Section: Discussionmentioning
confidence: 50%
“…Dysregulated cholesterol homeostasis is implicated in several human pathologies, including cancer, cardiovascular and neurodegenerative disease [19,20]. Mammalian cells have developed sophisticated mechanisms to prevent abnormal accumulation of cholesterol in cellular membranes [21].…”
Section: Of 15mentioning
confidence: 99%
See 1 more Smart Citation
“…We showed recently that human fibroblasts release sterol-rich vesicles of varying sizes during efflux and observed that at least a portion of such vesicles were shed directly from the PM (Juhl et al, 2021b). Such so-called ectosomes have been observed in a variety of cell systems, and they have been associated with cholesterol efflux in several cell types, for example in macrophages and in migrating cancer cells (Ma et al, 2015;He et al, 2018;Juhl and Wüstner, 2022). We found that the abundance of vesicles released from cells correlates with the activity of ABCA1 at the PM, which might work in tandem with NPC2 to export cholesterol from cells (Juhl et al, 2021b).…”
Section: A Lag Time Model Describes Sterol Efflux From Cells Via Form...mentioning
confidence: 99%
“…Regulation of this trafficking pathway is complex and ensures sufficient cholesterol supply but also prevention of cholesterol accumulation (Goldstein et al, 2006;Juhl and Wüstner, 2022).…”
Section: Introductionmentioning
confidence: 99%